Wide range of perioperative drugs and doses used in inguinal hernia repairs for premature infants - Dorismond, Christina (J Perinatol, 2020)
OBJECTIVE: Characterize the types and doses of commonly administered perioperative drugs in inguinal hernia (IH) repair for premature infants. STUDY DESIGN: Single-center, retrospective cohort study RESULTS: In total, 112 premature infants underwent IH repair between 2010–2015. Twenty-one drugs were used during IH repair, with each infant receiving a median 7 drugs. Acetaminophen (88%), bupivacaine (84%), cisatracurium (74%), sevoflurane (72%), and propofol (71%) were the most commonly used agents. Thirty-two infants underwent additional procedures with IH repair. Additional procedures were not associated with a higher number of perioperative drugs, however infants with additional procedures were exposed to higher cumulative doses of cisatracurium (p<0.001) and fentanyl (p=0.002). CONCLUSION: There is wide variability in the drugs and doses used for a common surgical procedure in this population, even within a single center. Future research should focus on the safety and efficacy of the most commonly used perioperative drugs described in this study.